Answer:
Step-by-step explanation:
1.
[tex]5\frac{3}{4} +(-\frac{1}{4} )\\\\5\frac{3}{4}=\frac{5\times4+3}{4}=\frac{23}{4}\\\\\frac{23}{4} +(-\frac{1}{4} )\\\\=\frac{23}{4}-\frac{1}{4}\\\\=\frac{23-1}{4}\\\\=\frac{22}{4}\\\\=5\frac{1}{2}[/tex]
2.
[tex]-\frac{2}{3} +\frac{1}{6} \\\\L.C.M \:OF\:3,6\: =6\\\\Adjust\:fractions\:based \:on \:their\:L.C.M\\\\=-\frac{4}{6}+\frac{1}{6}\\\\=-\frac{4}{6}+\frac{1}{6}\\\\=\frac{-3}{6}\\\\=-\frac{3}{6}\\\\=-\frac{1}{2}[/tex]
3.
[tex]-\frac{8}{5} +(-\frac{3}{4} )\\\\L.C.M \:OF\:5,4\: =20\\\\Adjust\:fractions\:based \:on \:their\:L.C.M\\\\=-\frac{32}{20}-\frac{15}{20}\\\\=\frac{-32-15}{20}\\\\=\frac{-47}{20}\\\\=-\frac{47}{20}\\\\=-2\frac{7}{20}[/tex]